2021
DOI: 10.3390/f12111527
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Wood Based on Near-Infrared Spectra and Four Gray-Level Co-Occurrence Matrix Texture Features

Abstract: Identifying wood accurately and rapidly is one of the best ways to prevent wood product fakes and adulterants in forestry products. Wood identification traditionally relies heavily on special experts that spend extensive time in the laboratory. A new method is proposed that uses near-infrared (NIR) spectra at a wavelength of 780–2300 nm incorporated with the gray-level co-occurrence (GLCM) texture feature to accurately and rapidly identify timbers. The NIR spectral features were determined by principal compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The comparison of the results is also done via a database. The creation of the database is complicated by the lack of standards of the equipment, the software, the settings and the nature of the samples in the procedure [49,53]. The method is particularly suitable for determining the moisture content of wood in the mill [54].…”
Section: Passive Samplingmentioning
confidence: 99%
“…The comparison of the results is also done via a database. The creation of the database is complicated by the lack of standards of the equipment, the software, the settings and the nature of the samples in the procedure [49,53]. The method is particularly suitable for determining the moisture content of wood in the mill [54].…”
Section: Passive Samplingmentioning
confidence: 99%
“…Figure 4 shows that the classification accuracy of transverse sections was higher than that of radial and tangential sections by using the above 6 feature classification methods. Pan et al (2021) concluded that GLCM incorporated with near-infrared (NIR) spectral features can rapidly identify wood, and that transverse sections contain more distinguishable wood features than the tangential and radial sections.…”
mentioning
confidence: 99%